Penanaman Nilai-Nilai Karakter pada Suporter Sepakbola Cyberxtreme PERSIK Kediri - Qinanda, Aurafadhil Hariz; Hady, Nuruddin (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This study aims to find out how efforts to instill character values are conducted by Persik Kediri cyberxtreme football supporters through the web and social media. This study uses a qualitative approach with a case study type of research. Data collection through observation, interviews, and documentation studies. The character values instilled in supporters’ activities are religious, integrity, nationalist, cooperation, and independence with clarity in their activities conducted during matches as well as activities outside the match or not related to football. Activities conducted include social service, breaking fast together, distributing takjil, making pictures or writing with calligraphy, making t-shirts and merchandise to sell. Cultivating character through various activities and using social media has been quite successful in changing supporter behavior in a more positive direction. Social media is a means for conveying information and discussions between members and administrators